The Effect of Different Heating Patterns on Vacuum Freeze‐Drying of Litchi Pulp. Issue 4 (26th April 2012) - Qiao, Fang; Fang, Changfa; Huang, Luelue; Zhang, Shufei
<x xml:space="preserve">Abstract</x> ABSTRACT Three heating patterns, constant temperature, temperature programmed and programmed cooling process were applied to freeze‐drying (FD) the litchi pulp in order to obtain the optimal FD heating technology. The results show that the three patterns all could be used to FD litchi pulp while the appearance was maintained well. The drying time of FD litchi pulp using programmed cooling process was the shortest among the three optimal heating patterns and the drying time was reduced by 15.8 and 11.6% comparing that of FD using constant temperature and temperature programmed. Higher temperature can be applied at the early primary drying stage when the temperature of litchi pulp is under the eutectic temperature and at secondary drying stage but should not be used at the later primary drying stage. PRACTICAL APPLICATIONS Vacuum FD is widely used in food, protein and drug drying. It is still the best drying method to obtain high‐quality biological products. The objective of this paper was to optimize the FD process of litchi pulp. The significance of this research can improve the efficiency of FD in litchi pulp drying. Throughout the trial, the production‐scale vacuum freeze‐dryer was used, which means that the FD process can provide technological support to produce freeze‐dried litchi pulp. In addition, it can also provide a reference for other fruits and vegetables' FD process optimization.